2004
DOI: 10.1038/sj.ijo.0802664
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high fat diet on body weight and mammary tumor latency in MMTV-TGF-α mice

Abstract: OBJECTIVE:The role of high fat diets in breast cancer/mammary tumor (MT) development is controversial. This may be partially attributable to variable effects of high fat diets on body weight. Here, we used a moderately high fat diet (32.5% fat calories) expected to cause obesity in most mice, but predicted to result in some mice remaining in the weight range of mice fed the low fat diet (11% fat calories). This provided the opportunity to compare mice fed the high fat diet exhibiting different body weights and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 44 publications
1
42
1
Order By: Relevance
“…These studies may suggest that the mammary gland microenvironment can affect cellular growth. In agreement with this hypothesis, studies by Cleary et al 44 have demonstrated that a highfat diet and increased adiposity may accelerate tumor formation in a mouse model of breast cancer.…”
Section: Diet Cholesterol and Cancermentioning
confidence: 57%
“…These studies may suggest that the mammary gland microenvironment can affect cellular growth. In agreement with this hypothesis, studies by Cleary et al 44 have demonstrated that a highfat diet and increased adiposity may accelerate tumor formation in a mouse model of breast cancer.…”
Section: Diet Cholesterol and Cancermentioning
confidence: 57%
“…In both cases these obese mice did not develop MT while their lean counterparts had tumor incidence rates comparable to that of the originally described MMTV-TGF-a mice [33]. However, when this transgenic mouse strain was subjected to dietary-induced obesity, mammary tumor latency was shortened for these hormone-responsive tumors [34]. Interestingly, in a second strain of transgenic mice, MMTV-neu, that develop ER-negative tumors, there were few differences in mammary tumor development between dietary-induced obese and lean mice [35].…”
Section: Introductionmentioning
confidence: 76%
“…Most studies that find a positive relationship between adiposity and carcinogenesis have not been designed to test whether the relationship between obesity and cancer is causal (4,7,8,(10)(11)(12)(13)(14)16). In such studies, the adiposity was not an independent variable itself and the connection between adiposity and carcinogenesis, thus, might have arisen because both were regulated by the same underlying factor(s).…”
Section: Discussionmentioning
confidence: 99%